Pengaruh Desain Kemasan, Positioning Merek Dan Kekuatan Merek Terhadap Citra Merek - Widjojo, Adi S; V, Eva (Jurnal Ilmiah Manajemen Kesatuan, 2018)
The purpose of this study were (1) to acquire the influence of packaging design to the brand image Teh Gelas, (2) to know how the influence of brand positioning to the brand image Teh Gelas, (3) to know how the influence of the strength of the brand to the brand image Teh Gelas, and (4) to find out how the effect of packaging design, brand positioning and brand strength altogether to the brand image Teh Gelas.The results showed that the determination coefficient regression model derived from the value adjusted R2 of 0,496 square. This means 49,6% Brand Teh Gelas Orang Tua Group can be explained by the variable packaging design, brand positioning and brand strength of the brand image, while 50,4% could be explained by other variables not included in the model